RETROSPECTIVE STUDY OF VERTICAL GROUND DEFORMATION IN COMO, NORTHERN ITALY: INTEGRATION OF LEVELLING AND PSI MEASUREMENTS - R. Eskandari; M. Scaioni (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
Subsidence-related vertical ground deformation due to natural and anthropogenic factors may lead to considerable damages to structures and infrastructures, and may increase the occurrence probability of consequential events, such as floods, especially on sea and lake shores. Como city, placed in the north of Italy, adjacent to Como Lake, is subjected to significant subsidence phenomenon, which has been monitored by geodetic levelling networks. In this work the historical geodetic levelling measurements and satellite-based Synthetic Aperture Radar (SAR) data archive are integrated to assess the accuracy of Atmospheric Delay and Deformation Rate estimations obtained through Persistent Scatter Interferometry (PSI) techniques. Tree levelling measurement datasets acquired in 1990, 1997 and 2004 are used in order to obtain the precise deformation rate at the benchmarks for two periods of 1990–1997 and 1997–2004. For multi-temporal InSAR analysis, 106 SAR images (1992–2004) and 41 SAR images (1992–2004) in Ascending Track orbit from ERS-1/2 missions are used in this study. The assessment is performed through a statistical comparison between two sets of vertical land deformation rates obtained by integrated methods. The results of the validation represented a good consistency between deformation rates derived by both techniques. Also, this study has revealed the potential of SAR images acquired in gyro-less mode by ERS-2 mission (2001–2004) in terms of the estimation of ground deformation.